Traditional Decriminalization in a Digital World: Reconstructing Criminal Policy towards Bitcoin-Based Money Laundering in the Era of Decentralized Finance - Fadilah, Fadilah; Susanto, Deny; Akkapin, Supaphorn (Journal Evidence Of Law, 2025)
The emergence of Bitcoin and blockchain technology as a decentralized financial infrastructure has shaken the foundations of the conventional criminal justice system, particularly in addressing money laundering offenses. This study aims to evaluate the effectiveness of existing criminal policies and reformulate the criminal law approach toward anonymous and cross-jurisdictional digital assets. Using a legal-normative method and comparative analysis of international policies, it was found that policies overly reliant on formal financial institutions become irrelevant in detecting peer-to-peer blockchain transactions. This study proposes a model for reconstructing criminal policy based on the principles of responsive law, adaptive digital surveillance (RegTech and SupTech), and transnational jurisdictional cooperation. The findings of this study are expected to provide conceptual and practical contributions to the design of a relevant, progressive, and digitally grounded criminal justice system.